Contemporary processes of regional industrial changes in Poland – possible interpretations - Domański, Bolesław (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2015)
Radical institutional, structural and technological changes which took place in Polish manufacturing and mining in the last 25 years are a good reason to discuss changes in spatial organization of this sector. The author aims at identifying the main processes of spatial change of industrial activity in the country at regional scale. This leads to two fundamental questions. First, what are the major factors and mechanisms of the identified spatial industrial change, and second, to what extent industrial changes find expression in regional and local development in various parts of the country. The analysis of trends in the transformation era show that both endogenous and exogenous factors contributed to the industrial growth of metropolitan areas. This was particularly stimulated by skilled labor, market and transport accessibility. The developed regions of Western Poland - Lower Silesia and Greater Poland (Wielkopolska) benefited most of all. A relatively successful restructuring took place in the Upper Silesian Industrial District and to some extent in the Łódż region too. Old industrial regions of the Sudety Mountains and Staropolski were significantly affected by deindustrialization processes at the same time. It is interesting, that the role of manufacturing in non-metropolitan areas has not decreased in general. Industrial development mainly rested on endogenous factors here. The impact of governmental policy on spatial changes in Polish manufacturing and mining took place primarily by means of road investment (new motorways) rather than special economic zones.